2021
DOI: 10.1503/cjs.011519
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical practice guideline: evidence, recommendations and algorithm for the preoperative optimization of anemia, hyperglycemia and smoking

Abstract: Clinical practice guideline: evidence, recommendations and algorithm for the preoperative optimization of anemia, hyperglycemia and smoking F or most of the 20th century, the focus of research in surgery was improvements in intraoperative technique, which led to major technical paradigm shifts exemplified by the evolution of transurethral resection of the prostate, 1 laparoscopic cholecystectomy, 2 endovascular aneurysm repair 3 and total mesorectal excision for rectal cancer, 4 among many others. The late 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 163 publications
0
36
0
5
Order By: Relevance
“…In addition, recent, current, or chronic use of any of the following medications and substances increases the likelihood of an adverse outcome in any patient during the perioperative period, including corticosteroids, opioids, insulin, anticoagulants, proton pump inhibitors, cancer chemotherapy, immunomodulators, ethanol, tobacco, and illicit substances [ 20 ]. Institutions have implemented DTP-related process and practice changes at key times in the admission process, that is, six to eight weeks preoperatively (prehospital) to detect and manage anemia, hyperglycemia, and smoking [ 21 ], in the preadmission clinic [ 22 , 23 , 24 ], on admission during medication reconciliation [ 25 , 26 , 27 , 28 ], throughout hospital stay [ 29 , 30 ], and at discharge [ 31 , 32 ]. In addition, theater and ward-based activities to rationalize drug therapy [ 33 , 34 ] include identifying and avoiding or minimizing the use of potentially inappropriate medications for at-risk patient populations: (1) the American Geriatric Society’s (AGS) Beers list for older adults [ 35 ]; and (2) the KIDs list for children created by the Pediatric Pharmacy Association (PPA) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent, current, or chronic use of any of the following medications and substances increases the likelihood of an adverse outcome in any patient during the perioperative period, including corticosteroids, opioids, insulin, anticoagulants, proton pump inhibitors, cancer chemotherapy, immunomodulators, ethanol, tobacco, and illicit substances [ 20 ]. Institutions have implemented DTP-related process and practice changes at key times in the admission process, that is, six to eight weeks preoperatively (prehospital) to detect and manage anemia, hyperglycemia, and smoking [ 21 ], in the preadmission clinic [ 22 , 23 , 24 ], on admission during medication reconciliation [ 25 , 26 , 27 , 28 ], throughout hospital stay [ 29 , 30 ], and at discharge [ 31 , 32 ]. In addition, theater and ward-based activities to rationalize drug therapy [ 33 , 34 ] include identifying and avoiding or minimizing the use of potentially inappropriate medications for at-risk patient populations: (1) the American Geriatric Society’s (AGS) Beers list for older adults [ 35 ]; and (2) the KIDs list for children created by the Pediatric Pharmacy Association (PPA) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…One evidence-based guideline 32 was identified that presented recommendations that were broader in scope than this report; however, recommendations related to the management of pre-operative anemia were presented. Recommendations were developed by 2 reviewers based on a systematic review of evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Six SRs [16][17][18][19][20][21] including 3 with meta-analysis (MA), 16,17,19 4 RCTs, [22][23][24][25] 6 non-randomized studies, [26][27][28][29][30][31] and 1 evidence-based guideline 32 was included in this report.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…The preoperative period provides a unique opportunity to optimize all modifiable risk factors. Both nursing and medical evaluations should identify and address patient habits (such as smoking and excessive alcohol consumption) and comorbidities, such as ischemic heart disease, high blood pressure, sleep apnea, and malnourishment [ 14 , 15 , 16 ].…”
Section: Patient Optimizationmentioning
confidence: 99%